ANALISIS ZONASI BAHAYA LONGSOR MENGGUNAKAN METODE MULTI CRITERIA EVALUTION (MCE) DI DAS KAMPAR HULU - Tri Oktaviani; Iswandi Umar (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to (1) find out the existing conditions of the mainland zone if viewed from the slope, relative relief, land cover, wetness dan lithology criteria. (2) know the zoning of landslides in DAS Kampar Hulu. This is quantitative research with spatial descriptive approarch. The method that used to determine the existing conditions in DAS Kampar Hulu by using GIS application namely Arcgis 10.8 to do various processing, then a multi criteria evaluation was used to analysis the landslide hazard zonation with Analytical Hierarchy Process calculations. Based on the result of the study it is know that 1) the existing condition of the slope at DAS Kampar Hulu who dominant is a very gentle slope or < 15°; relative relief is devided into thre classes, the distribution of which is low class located in Pangkalan Koto Baru District, precisely in Nagari Pangkalan, Tanjung Pauh and Tanjung Balik; then medium class is spread out in Bukti Barisan subdistrict, namely Nagari Maek, Kapur IX district and Pangkalan Koto Baru district, Pricisely in Nagari Gunuang Malintang, Koto Alam, Pangkalan, Tanjung Pauh, dan Tanjung Balik; The dominant land cover criteria (vegetation density) are dense class land cover; wetnees criteria in general, the conditions in DAS Kampar hulu are described as humid, partly wet, flowing and seeping, but dry at the border of Bukit Barisan and Kapur IX Districts; The lithological criteria in DAS Kampar Hulu constist of various rock formations including the Tandung Kumbang, Telukkido, Bahorok, Tanjung Pauh members, Kuantan, Piedmont fans, Alam City Volcano, Pematang, Ombilin, Sihapas dan Amas Volcano 2) Landslide hazard zoning in DAS Kampar Hulu consist of three levels, namely a high hazard level with an area of 13,41% of the total area of the study, a moderate hazard level with an area of 48,14% and a dominant level and finallu a low hazaed level with an area od 38.45% of the total research area.